The University School as access road to the University of Granma (Original) (REDEL. Revista Granmense de Desarrollo Local, 2021)
At the present time the entrance to the universities is governed by different interests which can be personal, of the own universities or of the companies that look for talents in the precedent educations. The article has as objective to socialize the results in the organization and integration of the processes and contexts of vocational formation and professional orientation of the University School of the University of Granma that it favors the access and the entrance to the Cuban Superior Education in those careers that are deficit for the development of the town. They are exposed as results main elements of the work addresses and their methodological orientations for the creation of the University School and the attention to the students.
Keywords: university school; university of Granma; Cuban superior education